The origins of the idea of «rule of law» as the rule of law in political and legal Platonism - Башук, Олена Григорівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The article analyzes the Plato's practical suggestions of forming of a State and Legislation. There is a commonality Plato's ideas with the conception of a lawful state. It shows an inexhaustible source of decisions for further development this conception.